IMPLEMENTASI PENDEKATAN STEAM UNTUK MENINGKATKAN KEMAMPUAN LITERASI SAINS PADA SISWA SEKOLAH DASAR - Teni Okty Handayani; Tri Suminar; Sri Sumartiningsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The low level of scientific literacy among students in Indonesia demands more interactive learning innovations. This study aims to describe the implementation of this approach. STEAM (Science, Technology, Engineering, Art, Mathematics) in improving the science literacy skills of fifth-grade students at SDN Padarek III. Using a descriptive qualitative method with interview, observation, and documentation techniques, the data were analyzed using the Miles and Huberman model. The results of the study showed that the application of the scientific literacy approach STEAM consistently improved students' scientific literacy in each cycle, with indicators achieving a progressive increase from 74%, 85%, to 87%. This improvement was influenced by engaging learning factors, real-world practice, contextualization of the material with everyday life, and teacher competence in classroom management.